(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Alpinia galanga and Clerodendrum colebrookianum belonging to the Zingiberaceae and Verbenaceae family, respectively is known to have many physiological properties like anti-bacterial, anti-oxidant, anti-tumor, etc. Both the plant samples possess many admirable curative properties as traditional medicine for the treatment of various diseases and disorders. The aim of this work is to identify the phytochemical and elemental components of both plant extracts which will support the therapeutic and traditional use of both plant samples. The presence or absence of micro- and macro-elements in the extracts was determined using atomic absorption spectrometry (AAS). Phytochemical analysis of the acetone and ethanol extract of both the plant samples also showed the presence of some necessary phytochemicals. Two in-vitro techniques (2,2-diphenylpicrylhydrazyl (DPPH) and ferric reducing antioxidant capacity (FRAP) assay where the absorbance was measured at 517 and 700 nm, respectively) were used to assess antioxidant activity, and ascorbic acid and trolox were used as the reference standard. For the DPPH assay, the highest activity (IC50 = 54.82 μg/mL) was shown by the acetone extract of C. colebrookianum, and the lowest (IC50 = 67.41 μg/mL) was shown by the acetone extract of A. galanga. The anti-microbial studies also revealed that the best activity was shown by the acetone extract of C. colebrookianum leaves against Escherichia coli i.e., 12 mm with minimal inhibitory concentration (MIC) value of 0.117 mg/mL.